The study of lyrical content based on Islamic view focusing on the halal and haram. Case study: the healer/ hip-hop by Erykah Badu, insya Allah by Maher Zain and shout to the lord by Darlene Zschech / Siti Nur'amalina Hairuddin - Hairuddin, Siti Nur'amalina (2010)
The purpose of the study is to identify Halal and haram lyrics in Islam and will be discussing on how the lyric turns Halal or Haram according to the Islamic law. This study will benefit Muslims and Non-Muslims who are interested in this matter. It is purposely studied to give the people a thou rough understand and realize what are the connection between Music, Singing and Islam is in daily life. The status and legality of music and singing have always confused a lot of Muslims mind due to the different arguments hold by Muslim jurists since music was created. Some of the jurists and scholars will allow singing but some of them have some strict restrictions on singing. This research is to identify lyric content according to rules (shari'ah) of Islam. There will be a discussion about the element of lyrics content according to 'shari'ah, aqidah and akhlak' and it is the differences culture and genre of song they will provide the status of Halal or Haram in singing. The findings will help Muslims and Non-Muslims understand which songs adhere to the regulations.